'Hard to Reach' or Nomadic Resistance? Families 'Choosing' Not to Participate in Early Childhood Services. Issue 3 (September 2013) - Osgood, Jayne; Albon, Deborah; Allen, Kim; Hollingworth, Sumi
Taking seeming disinterest in early years music-making as its focal point, this article explores the Deleuzian notion of (affect)ive assemblages to consider the relationships between formal early childhood services, the familial home environment of the 'hard to reach, ' and the use of populist musical resources. In drawing on post-structuralist and feminist theorisations of performance, subjectivity, language and meaning, the authors illustrate how discursive practices work at pathologising so that families are both contained and known within the nomenclature of 'hard to reach'. The article then moves to work with a number of Deleuzian concepts, including 'smooth/striated space' as well as 'nomad/nomadic'. In so doing, they illustrate nomadic resistance where new musical identities and affective relations between children, their families and musicality become possible for this elusive tribe. This article, understood as a rhizomatic journey, offers a conceptual stutter so as to destabilise dominant constructions about particular families. The lens of enquiry focuses upon the configuration of one white working-class family headed by a young single mother. In the English context, such parents have become routinely pathologised and labelled 'Chav Mums', yet this Deleuzoguattarian-inspired exploration seeks to offer a means of unsettling normative assumptions about family practices and the 'becoming' child within them, which will serve to inform social justice debates in other global contexts.